Elder self-neglect and abuse and mortality risk in a community-dwelling population - Dong, XinQi; Simon, Melissa; de Leon, Carlos Mendes; Fulmer, Terry; Beck, Todd; Hebert, Liesi; Dyer, Carmel; Paveza, Gregory; Evans, Denis (JAMA-Journal of the American Medical Association, 2009)
Context Both elder self-neglect and abuse have become increasingly prominent public health issues. The association of either elder self-neglect or abuse with mortality remains unclear. Objective To examine the relationship of elder self-neglect or abuse reported to social services agencies with all-cause mortality among a community-dwelling elderly population. Design, Setting, and Participants Prospective, population-based cohort study (conducted from 1993 to 2005) of residents living in a geographically defined community of 3 adjacent neighborhoods in Chicago, Illinois, who were participating in the Chicago Health and Aging Project (CHAP; a longitudinal, population-based, epidemiological study of residents aged ¿= 65 years). A subset of these participants had suspected elder self-neglect or abuse reported to social services agencies. Main Outcome Measures Mortality ascertained during follow-up and by use of the National Death Index. Cox proportional hazard models were used to assess independent associations of self-neglect or elder abuse reporting with the risk of all-cause mortality using time-varying covariate analyses. Results Of 9318 CHAP participants, 1544 participants were reported for elder self-neglect and 113 participants were reported for elder abuse from 1993 to 2005. All CHAP participants were followed up for a median of 6.9 years (interquartile range, 7.4 years), during which 4306 deaths occurred. In multivariable analyses, reported elder self-neglect was associated with a significantly increased risk of 1-year mortality (hazard ratio [HR], 5.82; 95% confidence interval [CI], 5.20-6.51). Mortality risk was lower but still elevated after 1 year ( HR, 1.88; 95% CI, 1.67-2.14). Reported elder abuse also was associated with significantly increased risk of overall mortality (HR, 1.39; 95% CI, 1.07-1.84). Confirmed elder self-neglect or abuse also was associated with mortality. Increased mortality risks associated with either elder self-neglect or abuse were not restricted to those with the lowest levels of cognitive or physical function. Conclusion Both elder self-neglect and abuse reported to social services agencies were associated with increased risk of mortality. JAMA. 2009; 302(5):517-526 www.jama.com
290 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/064-145-016-708-660 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: Activities of Daily Living; Aged; Aged; 80 and over; Cause of Death; Chicago; Cognition; Elder Abuse; Female; Humans; Male; Mandatory Reporting; Parkinson disease; Proportional Hazards Models; Prospective Studies; Risk; United States; Urban Population; abuse; aged; aging; article; cardiovascular disease; cause of death; cognition; cohort analysis; crime; daily life activity; demography; dept.hhs; diabetes mellitus; educational status; ethnic and racial groups; female; follow up; hazard ratio; hip fracture; human; hypertension; informed consent; longitudinal study; major clinical study; male; mandatory reporting; mortality; neoplasm; outcome assessment; physical activity; population based case control study; priority journal; proportional hazards model; prospective study; public health; research subject; risk; self neglect; social work; socioeconomics; statistics; stroke; urban population